Examination of the Relationship Between Occupational Professionalism and Occupational Alienation in Kindergarten Teachers - Öztabak, Muhammet Übeydullah (Rhapsode, 2021)
The aim of this study is to investigate the relationship between the levels of occupational professionalism and occupational alienation in kindergarten teachers. Correlational survey model among the quantitative research models was used in the research. In this context, 224 kindergarten teachers were reached via convenience sampling model. The data of the research was collected via the Teacher Information Form, Teachers’ Occupational Professionalism Scale and Occupational Alienation of Preschool Teachers Scale. SPSS software and statistical measures such as independent samples t-test, ANOVA and Pearson’s Product-Moment Correlation were used to analyse the obtained data. According to the research findings, both occupational professionalism and occupational alienation levels of kindergarten teachers were found to be high. Levels of occupational professionalism and occupational alienation may differ according to some demographic variables among teachers. The relationship between occupational professionalism and occupation alienation was found to be statistically significant. The same is also true for the sub-dimensions of the scales. Lastly, the findings and results obtained during the research were discussed in the light of the literature and suggestions were made.
Keywords: Kindergarten Teacher; Occupational Alienation; Occupational Professionalism; Teacher Alienation; Teacher Professionalism